2015
DOI: 10.1681/asn.2013111233
|View full text |Cite
|
Sign up to set email alerts
|

ANCA as a Predictor of Relapse

Abstract: The value of measuring ANCA during follow-up to predict a relapse is controversial. On the basis of recently obtained pathophysiologic insights, we postulated that measuring ANCA is useful in patients with renal involvement but is less valuable in patients with nonrenal disease. One hundred sixty-six consecutive patients with ANCA-associated vasculitis, positive for either proteinase 3 (PR3)-ANCA or myeloperoxidase (MPO)-ANCA, were included in our study, followed at regular intervals, and tested for PR3-ANCA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
183
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 191 publications
(194 citation statements)
references
References 35 publications
(52 reference statements)
7
183
1
3
Order By: Relevance
“…One study found that a combination of a rise of PR3-ANCA and C-ANCA was most predictive of a relapse [88]. However, this was not confirmed by a later study [27]. Preliminary results suggest that the second-and third-generation tests predict relapses better than IF tests and/or first-generation tests [2,80].…”
Section: Serial Anca Measurements -Heterogeneity Between Studiesmentioning
confidence: 92%
See 4 more Smart Citations
“…One study found that a combination of a rise of PR3-ANCA and C-ANCA was most predictive of a relapse [88]. However, this was not confirmed by a later study [27]. Preliminary results suggest that the second-and third-generation tests predict relapses better than IF tests and/or first-generation tests [2,80].…”
Section: Serial Anca Measurements -Heterogeneity Between Studiesmentioning
confidence: 92%
“…For example, it can be difficult to differentiate minor symptoms, such as fever or arthralgia that are caused by vasculitis from symptoms that are caused by an infection. Therefore, in our studies, a minor relapse was diagnosed only if symptoms were refractory to appropriate antibiotic therapy [27]. In addition, a relapse was defined as reoccurrence or new onset of …”
Section: Definitions Of Remission and Relapsementioning
confidence: 99%
See 3 more Smart Citations